Romantisisme pada Karya-Karya Raden Saleh: Suatu Tinjauan Kritik Seni - Annisa Desmiati; Yustiono Yustiono; Agung Hujatnika (ITB Journal Publisher, LPPM ITB, 2013)
Raden Saleh is a 19th century Indonesian painter who had the opportunity to master the European paintings in his time. He was born in Terbaya, Semarang on 1807 from a noble family. He then studied painting under the Belgian painter A.A.J. Payen who was assigned by Dutch colonial ruler to capture Indonesian scenery. After studied for some times in Indonesia, he began to travel to Netherlands, Germany, France, and several other European countries and chiseled his name as a famous Romantic painter both in Europe and in Indonesia. This research began from a predicament on how far Romanticism has its influence on Raden Saleh